(untitled) (Analysis in Theory and Applications, 2020)
Let T^k,1 be the singular integrals with variable Calderόn-Zygmund kernels or ± I (the identity operator), let T^k,2 and T^k,4 be the linear operators, and let T^k,3=± I. Denote the Toeplitz type operator by T^b=_k=1^t(T^k,1M^bI_α T^k,2+T^k,3I_α M^b T^k,4), where M^bf=bf, and I_α is the fractional integral operator. In this paper, we investigate the boundedness of the operator on weighted Lebesgue space when b belongs to weighted Lipschitz space.